2002
DOI: 10.1038/sj.leu.2402621
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to low concentrations of etoposide reduces the apoptotic capability of leukaemic cell lines

Abstract: The use of topoisomerase inhibitors has been associated with the development of secondary malignancies, suggesting that these agents can induce DNA damage that may be persistent. We have investigated the effect of short exposures (Ͼ3 days) to low etoposide concentrations (LC-etoposide, 0.01-0.04 M) on the ability of leukaemic cells to initiate apoptosis. Results showed that although LC-etoposide had no effect on cell growth characteristics, the pre-culture of cells with LC-etoposide conferred resistance to sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
2
7
0
Order By: Relevance
“…Bleibel et al 15 reported half maximal inhibitory concentrations (IC_50) slightly below 1 μM, suggesting that effects are also present at LC of etoposide. These conclusions are confirmed by Liu et al, 16 who also found that a lower limit for etoposide-induced proliferation and viability reduction occurs at ∼0.02 μM and also shows effects on the cell cycle at concentrations <1 μM (although for different cell lines). Even lower concentrations were reported to cause changes in phenotype and potentially also cause drug resistance or cause secondary leukemia.…”
supporting
confidence: 79%
“…Bleibel et al 15 reported half maximal inhibitory concentrations (IC_50) slightly below 1 μM, suggesting that effects are also present at LC of etoposide. These conclusions are confirmed by Liu et al, 16 who also found that a lower limit for etoposide-induced proliferation and viability reduction occurs at ∼0.02 μM and also shows effects on the cell cycle at concentrations <1 μM (although for different cell lines). Even lower concentrations were reported to cause changes in phenotype and potentially also cause drug resistance or cause secondary leukemia.…”
supporting
confidence: 79%
“…Our analyses show that POx formulation increased drug exposure in the CNS, in both medulloblastoma and forebrain and reduced systemic exposure, providing an explanation for both improved anti-tumor effect and reduced toxicity. Although low doses of vismodegib can induce a pharmacodynamic response, exposure to sub-optimal concentrations of cytotoxic drugs is associated with development of resistance and failure to respond to treatment (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…These results could have important implications for elucidating the mechanisms associated with the development of secondary malignancies (principally acute mielocitic leukemia) that are associated with the use of etoposide as an antineoplastic drug [50]. …”
Section: Resultsmentioning
confidence: 99%